Penggunaan media elektronik dalam pembelajaran: tinjauan terhadap kemahiran penggunaan internet di kalangan pelajar sarjana pendidikan KUiTTHO - Mohamed, Md. Ashraf (2001)
The purpose of this study is to investigate the skills of using the internet among Master of Education students at KUiTTHO. The survey is conducted to determine whether they are using the internet for academic purposes. In addition, the study is to seek the accomodation and training programme prepared by KUiTTHO as well as whether the skills of using internet are different by semester. The methodological approach of this study is done by data collection from questionaires. 196 students have been randomly selected as respondents to represent a population of 397. The data were analysed using Statistical Packages for Social Sciences (SPSS) version 10. The data analysis has been described quantitatively to get values of frequencies, percentages and means. The results show that students who have skills in using internet spending more time for academic purposes. The results also show skills in using the internet are not different by semester. It should be emphasized here that KUiTTHO is still not accomodating satisfied internet facilities and training programmes prepared for students in context to increase their skills in using internet which is one of the most important application of information technology today.